A Noncovalent Photoswitch for Photochemical Regulation of Enzymatic Activity. (3rd May 2022) - Chai, Jingshan; Zhao, Yu; Xu, Lina; Li, Qiushi; Hu, Xin‐Yue; Guo, Dong‐Sheng; Liu, Yang
Abstract: Photochemical regulation provides a promising approach for controlling enzyme activity on demand owing to its high spatiotemporal resolution. However, reversible regulation of the enzyme activity by light usually requires genetic mutations and covalent modifications of the target enzymes, which may lead to irreversible changes in the enzyme structure and subsequent loss of the enzymatic activity. Herein, we have developed a novel strategy based on a polymeric inhibitor‐encapsulated enzyme, which noncovalently anchors the azobenzene‐modified inhibitors to the enzyme active site, thereby achieving reversible control of the activity of native enzymes using light. As neither genetic mutation nor chemical modification of enzymes is required for this method, negligible loss of the enzymatic activity was observed for the encapsulated enzymes compared to their native counterparts. Thus, this approach has demonstrated a promising strategy for achieving reversible regulation of the activity of native enzymes. Abstract : A noncovalent photoswitch for regulating enzyme activity was synthesized based on a polymeric inhibitor‐encapsulation method. This method noncovalently anchors an azobenzene‐modified inhibitor to the active site of the encapsulated enzyme, allowing reversible control of the enzymatic activity using light. This approach provides a promising strategy to regulate the activity of the enzymes without genetic mutation nor chemical modification of enzyme.